PENGEMBANGAN ASESMEN BERBASIS KURIKULUM 2013 UNTUK MENGUKUR KEMAMPUAN BERFIKIR KRITIS GURU IPA SMP NEGERI KABUPATEN DONGGALA - Ika Istadewi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2020)
The purpose of this study was to develop a 2013 curriculum-based test assessment to measure the critical thinking skillsof science teachers at the State Junior High School in Donggala Regency. This type of research is research using theResearch and Development (R & D) method which refers to the Plomp development model which consists of severalphases, namely: (1) Initial Investigation Phase, (2) Design phase, (3) Realization, (4) ) Test, evaluation and revisionphases. As a sample in this study were 30 Natural Sciences teachers at Donggala Regency Public Middle School. Datacollection methods in research and development include: (1) Preliminary studies, (2) Making 2013 curriculum-basedassessment tests and (3) Testing and refinement of assessment tests. The test used is a description test to measure theability of science teachers in developing critical thinking skills through a 2013 curriculum-based assessment test. Thedata analysis technique used is a descriptive qualitative technique with validity, reliability, difficulty and differentiationlevels.The results of the study concluded that the development of the 2013 curriculum-based assessment test could measurethe critical thinking skills of science teachers at the State Junior High School in Donggala Regency. This is shown fromthe results of the evaluation of the test instruments by material experts, design and practitioners showed very goodcategories with an average percentage of assessments between 85.47% to 90.71%. The results of the validity test of thecritical thinking tests of the ten indicators used as items in the study were valid using a 5% significance level, thereliability test results obtained an average value of 0.95 which is greater than the average rtabel so that the level ofreliability is very High, for the level of difficulty of the category classified as Medium category and the category ofDifficulties and the test of distinguishing questions based on the analysis of the tests are classified as Very Good, Goodand Enough.